«Unbewaffnetes Auge»: Benjamin’s interpretation of comedy in Shakespeare and Molière - Alice Barale (Aisthesis, 2019)
This essay examines two texts that Walter Benjamin wrote in 1918, during his period in Bern, on Shakespeare’s comedy As you like it and on Le malade imaginaire by Molière When these texts are considered together, a question arises. What is the role of the comic inside Benjamin’s philosophy, in this period and also in the years to follow? Is the comic really only the other side of mourning, as Benjamin writes in The Origin of German Tragic Drama, or does it also have another significance, a significance of its own? Moreover, why should Shakespeare’s comedy be the opposite of Molière’s comedy, as Benjamin writes in the paper on Molière? In order to answer, we are going to set a connection between Shakespeare’s «unarmed eye» (As you like it) and the «innocence» (Fate and Character) that Molière’s comedy indicates. This will also lead us to another text that was of much significance to Benjamin (GB, 02/02/1920 et al.), Stendhal’s Charterhouse of Parma. Here too, as in As you like it, there is an innocent protagonist trying to escape from the evil of a court. Yet Shakespeare’s As you like it ends with the reconstruction of a court. What does Benjamin mean, then, when he states that in As you like it «everything ends in loneliness»? The answer will provide a point of convergence between Shakespeare’s and Molière’s comedy. Benjamin’s idea of «Weltlichkeit» (ibid.), of which comedy is a necessary part, will prove to be an alternative to the “armed” character of the court.